1998
DOI: 10.1021/la970216n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Counterions and Headgroup Hydrophobicity on Properties of Micelles Formed by Alkylpyridinium Surfactants. 2. Microcalorimetry

Abstract: Citation for published version (APA): Bijma, K., Blandamer, M. J., & Engberts, J. B. F. N. (1998). Effect of counterions and headgroup hydrophobicity on properties of micelles formed by alkylpyridinium surfactants. 2. Microcalorimetry. Langmuir, 14(1), 79 -83. DOI: 10.1021/la970216n Copyright Other than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…The sample cell was stirred (350 rpm) to ensure complete mixing. It had been shown previously (13) that the stirring speed has no effect on the recorded enthalpograms for the deaggregation of micelles. We confirmed this observation by repeating a number of experiments using a stirring speed of 800 rpm.…”
Section: Titration Microcalorimetrymentioning
confidence: 83%
See 1 more Smart Citation
“…The sample cell was stirred (350 rpm) to ensure complete mixing. It had been shown previously (13) that the stirring speed has no effect on the recorded enthalpograms for the deaggregation of micelles. We confirmed this observation by repeating a number of experiments using a stirring speed of 800 rpm.…”
Section: Titration Microcalorimetrymentioning
confidence: 83%
“…The effect of counterions is not completely clear. While Johnson and Olofsson (12) found a trend for aromatic counterions between the position of the counterions with respect to the headgroup area and the heat capacities, no such trend was observed by Bijma et al (13). The large negative isobaric heat capacities for vesicle formation are a consequence of the fact that the aggregates are formed through overlap of the thermally labile hydrophobic hydration shells (2).…”
Section: Methodsmentioning
confidence: 91%
“…Contrary to simple salts (class A), a large proportion of these counterions (∼80%) is assumed to be incorporated into the micelles. It was found that in CPCl-NaSal, long wormlike micelles are immediately formed at the cmc (0.04 wt.%), without passing through an intermediate spherical morphology [68,69,71].…”
Section: Physical Chemistry Of Wormlike Micelles and Related Systemsmentioning
confidence: 99%
“…The difference in enthalpy of dilution below and above the CMC was taken as the enthalpy of micelle formation (21).…”
Section: Titration Microcalorimetrymentioning
confidence: 99%